Educaciones emancipadoras de Nuestra América. Sujetos y procesos - González-Terreros, María Isabel; Ramos dos Santos, Arlete; Pinheiro-Barbosa, Lia (Revista Colombiana de Educación, 2020)
Presentación dosier